2002
DOI: 10.1038/sj.bjp.0704781
|View full text |Cite
|
Sign up to set email alerts
|

M3 muscarinic receptors mediate contraction of human urinary bladder

Abstract: Since muscarinic receptors appear to be the physiologically most important control system for urinary bladder contraction, we have characterized the receptor subtype mediating contraction in response to the muscarinic agonist carbachol in the human bladder. Experiments were based on four antagonists, the non-selective atropine, the M 1 -selective pirenzepine, the M 2 -selective methoctramine and the M 3 -selective darifenacin. All antagonists yielded Schild-plots with a slope close to unity. The order of poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
84
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(98 citation statements)
references
References 15 publications
8
84
1
2
Order By: Relevance
“…It is also possible that this variation observed in organ transplant donors re£ects the natural variation of normal human bladder contractile response. Possible explanations for the discrepancy between our ¢ndings and previous ¢ndings that only M 3 receptors mediate contraction of normal human bladder [Waldeck et al, 1997;Yono et al, 1999;D' Agostino et al, 2000;Chess-Williams et al, 2001;Fetscher et al, 2002;Miyamae et al, 2003;Schneider et al, 2004a] include not only di¡erences in the source of bladder tissue (cancer cystectomy vs. organ transplant donors) and averaging the data across all of the di¡erent subjects but also other methodologic di¡erences. All of the previous studies with the exception of our own have used each strip as its own control, repeating agonist concentration response curves up to ¢ve times in succession with increasing concentrations of the antagonists whereas in our studies each strip was exposed to only a single cumulative agonist concentration response curve either in the presence or absence of the antagonist in separate groups of strips.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…It is also possible that this variation observed in organ transplant donors re£ects the natural variation of normal human bladder contractile response. Possible explanations for the discrepancy between our ¢ndings and previous ¢ndings that only M 3 receptors mediate contraction of normal human bladder [Waldeck et al, 1997;Yono et al, 1999;D' Agostino et al, 2000;Chess-Williams et al, 2001;Fetscher et al, 2002;Miyamae et al, 2003;Schneider et al, 2004a] include not only di¡erences in the source of bladder tissue (cancer cystectomy vs. organ transplant donors) and averaging the data across all of the di¡erent subjects but also other methodologic di¡erences. All of the previous studies with the exception of our own have used each strip as its own control, repeating agonist concentration response curves up to ¢ve times in succession with increasing concentrations of the antagonists whereas in our studies each strip was exposed to only a single cumulative agonist concentration response curve either in the presence or absence of the antagonist in separate groups of strips.…”
Section: Discussioncontrasting
confidence: 93%
“…Although the muscarinic receptor subtype mediating contraction of the normal human bladder is thought to be the M 3 subtype, this is based on the following reports in a limited total number of human bladder specimens [Waldeck et al, 1997;Yono et al, 1999;D' Agostino et al, 2000;Chess-Williams et al, 2001;Fetscher et al, 2002;Miyamae et al, 2003;Pontari et al, 2004;Schneider et al, 2004a].These various studies have demonstrated that M 3 -selective antagonists such as 4-DAMP and darifenacin inhibit carbachol mediated contractions with high a⁄nity and M 2 -selective antagonists such as methoctramine inhibit contraction with low a⁄nity, concluding that the M 3 receptor mediates normal human detrusor contraction. In all of these reports other than our own, mean a⁄nity values are reported for the antagonists across all of the di¡erent bladder specimens, all of which were obtained at cystectomy for bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However the responses of isolated detrusor strips to muscarinic agonists are mediated via the minor population of M3 receptors (Sellers et al, 2000, Chess-Williams et al, 2001, Fetscher et al, 2002. A similar result was obtained in the urothelium and lamina propria.…”
Section: Discussionsupporting
confidence: 65%
“…These data suggest that in the human control detrusor the in vitro direct contractile responses to muscarinic stimulation are mediated via the M 3 receptor subtype. This result supports previous studies in the human detrusor [3,4]. In strips of detrusor muscle from neurogenic overactive or idiopathic overactive detrusor patients, there was no evidence of a shift in affinity from M 3 to M 2 for any of the muscarinic antagonist.…”
Section: Discussionsupporting
confidence: 91%
“…In human tissue M 3 but not M 2 antagonists have a high affinity for the receptor mediating contraction indicating in vitro functional responses to muscarinic receptor stimulation is mediated via the minor population of M 3 muscarinic receptors [3][4][5]. Similar findings have been reported in number of other species (for review see [6]).…”
Section: Introductionsupporting
confidence: 69%